Multicentre Experience with the Chimney Technique for Abdominal Aortic Aneurysms in French University Hospitals. (May 2020) - ,; Thaveau, Fabien; Soler, Raphael; Duprey, Ambroise; Ammi, Myriam; Desgranges, Pascal; Ducasse, Eric; Coggia, Marc; Allaire, Eric; Becquemin, Jean-Pierre; Cochennec, Frédéric; Kobeiter, Hicham; et al.
Abstract : Objective: The chimney technique (ChEVAR) allows for proximal landing zone extension for endovascular repair of complex aortic aneurysms. The aim of the present study was to assess ChEVAR national outcomes in French university hospital centres. Methods: All centres were contacted and entered data into a computerised online database on a voluntary basis. Clinical and radiological data were collected on all consecutive ChEVAR patients operated on in 14 centres between 2008 and 2016. Patients were deemed unfit for open repair. Factors associated with early (30 day or in hospital) mortality and type 1 endoleak (Type I EL) were calculated using multivariable analysis. Results: In total, 201 patients with 343 target vessels were treated. There were 94 juxtarenal (46.8%), 67 pararenal (33.3%), 10 Crawford type IV thoraco-abdominal (5%) aneurysms, and 30 (15.1%) proximal failures of prior repairs. The pre-operative diameter was 66.8 ± 16.7 mm and 28 (13.9%) ChEVAR were performed as an emergency, including six (2.9%) ruptures. There were 23 (11.7%) unplanned intra-operative procedures, mainly related to access issues. The rate of early deaths was 11.4% ( n = 23). The elective mortality rate was 9.8% ( n = 17). Nine patients (4.5%) presented with a stroke. The rate of early proximal Type I EL was 11.9%. Survival was 84.6%, 79.4%, 73.9%, 71.1% at 6, 12, 18, and 24 months, respectively. The primary patency of chimney stents was 97.4%, 96.7%, 95.2%, and 93.3% at 6, 12, 18, and 24 months, respectively. Performing unplanned intra-operative procedures (OR 3.7, 95% CI 1.3–10.9) was identified as the only independent predictor of post-operative death. A ChEVAR for juxtarenal aneurysm was independently associated with fewer post-operative Type I ELs (OR 0.17, 95% CI 0.05–0.58). Conclusion: In this large national ChEVAR series, early results were concerning. The reasons may lie in heterogeneous practices between centres and ChEVAR use outside of current recommendations regarding oversizing rates, endograft types, and sealing zones. Future research should focus on improvements in pre-operative planning and intra-operative technical aspects.